Doege-Potter Syndrome: A Presumptive Case of Metastatic Hemangiopericytoma with Persistent Hypoglycemia in a 27-Year-Old Male - Zarra, Von Lovel; Demegillo, Kenny Jun; Uyking-Naranjo, May; Domado, Ahmad (Journal of the ASEAN Federation of Endocrine Societies, 2021)
Doege-Potter syndrome (DPS) is a rare paraneoplastic condition characterized by hypoinsulinemic hypoglycemia from a solitary fibrous tumor. The underlying mechanism is the secretion of a prohormone form of insulin-like growth factor II (IGF-II) by the tumor, which causes decreased release of glucose into the circulation. We report the case of a 27-year-old Filipino male with presumptive DPS from a recurrent right temporo-zygomatic hemangiopericytoma (HPC). The complexity of DPS requires a multidisciplinary approach. Early screening for metastases from HPC may prevent the undesirable sequelae of the disease process.